Youtubers negras e o feminismo - Coelho, Mariana [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This paper relates the concepts of black feminism with questions about representativeness and empowerment of the black women on social media network. Based on the videos sharing site YouTube and on the videos produced by black, young, Brazilian, female youtubers. Aiming to understand how the black feminism and its influences are represented in these videos. Also analyzes the structure of two different channels, briefly comparing them as the type of content created and other digital medias of communication used by then. Besides that, discusses about the concepts of radical alternative media and its relation with the videos produced by the black youtubers

Este trabalho relaciona conceitos do feminismo negro com questões de representatividade e empoderamento da mulher negra nas redes sociais. Tomando como base o site de compartilhamento de vídeos YouTube e os vídeos produzidos por youtubers brasileiras, mulheres, jovens e negras. Visando compreender de que forma o feminismo negro e suas influencias estão representados nesses vídeos. Também analisa estruturalmente dois canais, fazendo breves comparações entre eles quanto ao tipo de conteúdo criado e outras mídias digitais de comunicação utilizadas. Além disso, discorre sobre conceitos de mídia radical alternativa e sua relação com os vídeos produzidos pelas youtubers negras
Keywords: Feminismo; Negras; Youtube (Recurso eletrônico); Youtube (Electronic resource)